Strategies for Zero-Downtime Cloud Migration of Oracle Databases - Karuppusamy, Mohammed (Journal of Research in Science and Engineering, 2026)
Enterprises are increasingly migrating mission - critical Oracle databases to the cloud to achieve scalability, cost savings, and operational efficiency. However, ensuring zero - downtime migration remains a critical challenge due to risks such as data inconsistency, performance degradation, and business disruptions. This research explores seamless Oracle database migration strategies using Oracle GoldenGate, Active Data Guard, and RMAN to enable real - time replication and incremental backups, ensuring uninterrupted database availability. The study highlights key best practices, including pre - migration planning, automated testing, real - time monitoring, and post - migration optimization. Additionally, this research introduces AI - driven automation to predict optimal cutover windows, minimize replication lags, and dynamically allocate cloud resources. It also investigates multi - cloud migration strategies and blockchain - based data verification to enhance data integrity and security. The findings provide a structured framework for enterprises to modernize their database infrastructure while ensuring business continuity, cost efficiency, and compliance.